1995
DOI: 10.2307/1941699
|View full text |Cite
|
Sign up to set email alerts
|

The Trade‐Offs Between Digestion Rate and Efficiency in Warblers and Their Ecological Implications

Abstract: Frugivory in birds is associated with rapid gut passage whereas insectivory is associated with slower gut passage. This is interpreted by some avian ecologists to reflect an inherent digestive constraint on diet selection, but it could also result from dietary acclimation. We predicted that Yellow—rumped Warblers (Dendroica cornata) acclimated to fruit—, insect—, and seed—based diets would exhibit retention time that increase in that rank order, because this is the rank order of retention time across species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 29 publications
3
126
1
Order By: Relevance
“…For birds maintaining constant body mass and body composition, time-averaged energy intake equals time-averaged energy use (Hammond and Diamond, 1997). This balance depends on the interplay between the intake and digestive processing of matter and energy and their allocation among diverse functions, including thermoregulation, growth and reproduction (Afik and Karasov, 1995;Starck and Rahmaan, 2003;Caviedes-Vidal et al, 2007). Increased food intake, hypertrophy of the gastrointestinal tract and the consequent increased absorption of nutrients may be viewed as responses by wintering birds to physical and biotic seasonal habitats (Novoa et al, 1996, McWilliams andKarasov, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For birds maintaining constant body mass and body composition, time-averaged energy intake equals time-averaged energy use (Hammond and Diamond, 1997). This balance depends on the interplay between the intake and digestive processing of matter and energy and their allocation among diverse functions, including thermoregulation, growth and reproduction (Afik and Karasov, 1995;Starck and Rahmaan, 2003;Caviedes-Vidal et al, 2007). Increased food intake, hypertrophy of the gastrointestinal tract and the consequent increased absorption of nutrients may be viewed as responses by wintering birds to physical and biotic seasonal habitats (Novoa et al, 1996, McWilliams andKarasov, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether a growth cost might reasonably be equated with the fitness cost described theoretically, I also examined the correlation between nestling growth and survival to independence. Finally, I investigated whether increased begging potentially incurred digestive costs by measuring the rate of fecal sac production, a known correlate of digestive efficiency (30).…”
mentioning
confidence: 99%
“…These results are in line with the nicotine tolerance of white-eyes, which was comparable to that of sunbirds at low sucrose concentrations (Lerch-Henning and Nicolson 2013). In addition, since assimilation efficiency is linked to retention time (Afik and Karasov 1995), it is not surprising that we found that high nicotine affected negatively both parameters. However, Cape white-eyes that are legitimate pollinators for Aloe vryheidensis are tolerant to phenolics in this nectar (Johnson et al 2006).…”
Section: Effect Of Nicotine On Digestive Performancementioning
confidence: 59%